Implementasi Sistem Rujukan Terintegrasi (Sisrute) di RSUD Dr. Soedarso - Annisa Pirlaily Pazriani; Cau Kim Jiu; Lidia Hastuti (Malahayati Nursing Journal, 2026)
ABSTRACT The implementation of health referrals in Indonesia still faces obstacles such as lack of coordination between health facilities and suboptimal use of technology. RSUD Dr. Soedarso has implemented the Integrated Referral System (SISRUTE), yet it still encounters challenges including "bypass" patients and technical constraints. This study aims to identify the implementation of SISRUTE, healthcare workers' perceptions, and the barriers and support in its implementation at RSUD Dr. Soedarso. This qualitative study with a phenomenological design involved SISRUTE operators, ER nurses, management, referrers, and patients' families selected through purposive sampling. Data were collected via semi-structured interviews, observation, and documentation, then analyzed using the Miles and Huberman model. The implementation of SISRUTE has successfully digitalized the referral mechanism through a more directed one-gate filtration system. However, its effectiveness is hindered by internet instability, low quality of data input from referring facilities, and a reliance on WhatsApp for emergency clinical coordination. SISRUTE significantly improves the efficiency and certainty of referral data. Its success heavily depends on management commitment, network infrastructure reliability, and the digital literacy of human resources. Keywords: SISRUTE, RSUD Dr. Soedarso, Nursing Management, Digital Health Transformation.  ABSTRAK Pelaksanaan rujukan di Indonesia masih terkendala koordinasi antar-faskes dan pemanfaatan teknologi yang belum optimal. RSUD Dr. Soedarso telah menerapkan Sistem Rujukan Terintegrasi (SISRUTE), namun masih menghadapi tantangan seperti pasien bypass dan kendala teknis. Penelitian ini bertujuan mengidentifikasi penerapan SISRUTE, persepsi tenaga kesehatan, serta hambatan dan dukungan dalam implementasinya di RSUD Dr. Soedarso. Penelitian kualitatif dengan desain fenomenologi ini melibatkan operator SISRUTE, perawat IGD, manajemen, perujuk, dan keluarga pasien melalui purposive sampling. Data dikumpulkan melalui wawancara semiterstruktur, observasi, dan dokumentasi, lalu dianalisis menggunakan model Miles dan Huberman. Implementasi SISRUTE berhasil mendigitalisasi mekanisme rujukan melalui filtrasi satu pintu yang lebih terarah. Namun, efektivitasnya terhambat oleh ketidakstabilan internet, rendahnya kualitas input data dari faskes perujuk, serta ketergantungan pada WhatsApp untuk koordinasi klinis darurat. SISRUTE meningkatkan efisiensi dan kepastian data rujukan secara signifikan. Keberhasilannya sangat bergantung pada komitmen manajemen, keandalan infrastruktur jaringan, dan literasi digital sumber daya manusia. Kata Kunci: SISRUTE, RSUD Dr. Soedarso, Manajemen Keperawatan, Transformasi Digital Kesehatan.